Plan B for Europe: The Birth of 'Disobedient Euroscepticism'?. (5th January 2022) - Bortun, Vladimir
Abstract: Despite attempts in the broader literature to go beyond a binary classification of party‐based Euroscepticism, Eurosceptic radical left parties are still generally divided into those advocating reform of the EU and those calling for an exit from the EU. The most notable exception is the classification proposed by Keith (2017), who distinguishes between Rejectionist, Conditional and Expansionist Euroscepticism. However, this article argues that a new form of left‐wing Euroscepticism has emerged since 2016, which does not fit with any of the existing classifications. It is the position put forward by 'Plan B for Europe', a transnational initiative of radical left parties, which advocates a disobedient approach towards the EU that simultaneously aims for the reformation of the latter while preparing for a break from it. This is a novel type of party‐based Euroscepticism that should supplement Keith's classification.